An 8-inch absorption grating used in cascaded Talbot-Lau interferometers for X-ray phase-contrast imaging. (6th November 2019) - Lei, Yaohu; Xu, Guiwen; Wali, Faiz; Li, Qiaofei; Liu, Xin; Huang, Jianheng; Li, Ji
Abstract: Cascaded Talbot-Lau interferometers (CTLI) facilitates X-ray differential phase-contrast imaging (DPCI) by using absorption gratings with large periods. Large-area gratings provide a large field of view (FoV), thus they extend applications of DPCI. However, conventional methods for fabricating such gratings are still costly. We report an 8 inch absorption grating that was fabricated by filling tungsten nanoparticles into grating structures. The fabrication process requires readily available equipment, allowing it to be easily implemented. We experimentally tested these absorption gratings with our X-ray CTLI system, yielding Moiré fringes and multi-contrast images, which demonstrates the effectiveness of our proposed method.